Características do processo de evasão do estudantes do curso de Ciências contábeis de uma universidade pública brasileira - Samuel de Oliveira Durso (2015)
The present study aimed to seek evidence to characterize the dropout process of Accounting students from a Brazilian public university. Its theoretical platform was formulated mainly by models of explanation of the dropout process proposed by Spady (1970, 1971), Tinto (1975), and Bean (1980), all of them related to the higher education context. The methodology of this research consisted of quantitative and qualitative steps, and the database was formed by 373 students of the undergraduate degree in Accounting from a public university (classes 2004/1 to 2009/1). Of the total number of observations, 266 refer to graduating individuals, whereas 107 are related to dropouts. In the quantitative phase, simple logistic regressions were estimated in order to identify the main socioeconomic and cultural factors affecting the propensity to evasion. Additionally, from a multiple logistic regression, an evasion forecasting model was outlined, tested, and validated according to the methodology proposed by Hair Júnior et al. (1998). In the qualitative part of the study, a survey was carried out through a questionnaire based on Cunha, Nascimento, and Durso (2014), and applied through the Google Docs platform to dropout individuals from the Accounting course of a public higher education institution. 22 answered questionnaires were received out of a total of 107 dropouts (20.6%). Of the 22 respondents, 5 agreed to concede a semi-structured interview. The interview script was adapted from Bardagi (2007). The qualitative phase of the study aimed to identify the main factors that influence evasion, in the view of dropouts themselves. As main results, the quantitative phase of the study showed that, from the 30 socioeconomic and cultural variables analyzed, 17 presented statistical significance for the occurrence of evasion in the context of the sample used. Among the statistically significant variables, some are linked to the inherent characteristics of the individuals whereas others are related to academic potential and characteristics of the high school they attended. Finally, some are related to the family financial status of the students. In addition, the evasion forecasting model, using eight socioeconomic and cultural variables, was able to predict correctly 77% of the cases of dropout and graduation for the sample used. The methodology employed to validate the model confirmed its predictive ability. The qualitative phase of the study showed that the sample participants had great participation in the labor market, both before and after graduation. It was also possible to determine that the dropouts from the Accounting course found it difficult to reconcile academic and professional activities. Most of the participants in the qualitative phase did not identify themselves with the teachers of the Accounting course in the institution analyzed. Finally, with regard to vocational issues, it became clear through the interviews that the dropouts do not present any problems concerning the professional activity in the Accounting field.